Closer view of the small Chhatri - Temples of India Project Team (Jio Institute, 2024)
A closer view of the small chhatri which is attached to the plinth of the temple. This chhatri is probably a memorial which was built here at a later date. It is made of marble stone and the steps connected to its pedestal are painted in the same manner as the main temple plinth.